2019
DOI: 10.1039/c8ay02613k
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of electrochemical surface-enhanced Raman spectroscopy (EC-SERS) signals for bacterial samples: the importance of filtered control studies in the development of new bacterial screening platforms

Abstract: The importance of filtered control studies for ascertaining the origin of bacterial SERS signals is highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Gram-positive B. megaterium and Gram-negative E. coli K-12 were detected and differentiated with improved SERS peak intensities and spectral richness, showing a promise for bacterial screening. Further coupled the EC-SERS method with filter system, control studies were performed to ascertain the EC-SERS signals for bacterial sample [139]. It was reported that the SERS spectra collected for bacterial cultures were due to the released small molecules metabolites in response to environmental stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Gram-positive B. megaterium and Gram-negative E. coli K-12 were detected and differentiated with improved SERS peak intensities and spectral richness, showing a promise for bacterial screening. Further coupled the EC-SERS method with filter system, control studies were performed to ascertain the EC-SERS signals for bacterial sample [139]. It was reported that the SERS spectra collected for bacterial cultures were due to the released small molecules metabolites in response to environmental stressors.…”
Section: Discussionmentioning
confidence: 99%
“…EC-SERS is a technology that combines electrochemistry and SERS. Recently, many analyses have shown that it greatly improves the sensitivity of SERS [ 16 , 17 ]. Brindersi et al [ 18 ] showed that Fabric-based electrodes provide excellent EC-SERS signals, allowing rapid detection of levofloxacin at clinically relevant concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of the specific adsorption of target species via EC-SERS for improved signal generation have been shown in previous research. Nonetheless, aside from two reports , focusing on using a classical EC-SERS approach for the detection of Gr + and/or Gr – , involving a 16 h and a 6 h preincubation, respectively; essentially, in the case of mycobacteria, EC-SERS is an underexplored area and has not been reported yet. Moreover, with classical EC-SERS on preformed silver nanometallic surfaces, positive voltages are usually strictly avoided due to the potential for oxidation and its associated negative impact on the SERS activity of the nanoparticles. , However, in this study, the application of a positive voltage forms an integral part of the EC-SERS detection technique.…”
mentioning
confidence: 99%